2022
DOI: 10.1016/j.uclim.2021.101059
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of air pollution variability during second wave of COVID-19 in Delhi, India

Abstract: To curb the 2nd wave of COVID-19 disease in April–May 2021, a night curfew followed by full lockdown was imposed over the National Capital Territory, Delhi. We have analyzed the observed variation in pollutants and meteorology, and role of local and transboundary emission sources during night-curfew and lockdown, as compared to pre-lockdown period and identical periods of 2020 lockdown as well as of 2018 and 2019. In 2021, concentration of pollutants (except O₃, SO₂, and toluene) declined by 4–16% during night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Saharan et al. ( 2022 ) shows higher measured surface pollutants in 2021 in Delhi, India compared to 2020, but still less than pre‐COVID; their Table 2 for both March and April shows reductions in CO, O 3 , and NO x during 2021 relative to years 2018 and 2019. Sarmadi et al.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Saharan et al. ( 2022 ) shows higher measured surface pollutants in 2021 in Delhi, India compared to 2020, but still less than pre‐COVID; their Table 2 for both March and April shows reductions in CO, O 3 , and NO x during 2021 relative to years 2018 and 2019. Sarmadi et al.…”
Section: Introductionmentioning
confidence: 95%
“…The general consensus is that global pollution was greater in 2021 compared to 2020, but still lower than in years prior to COVID-19. Saharan et al (2022) shows higher measured surface pollutants in 2021 in Delhi, India compared to 2020, but still less than pre-COVID; their This paper provides a global evaluation of reductions in free tropospheric ozone in years 2020 and 2021 during the COVID-19 pandemic using ozone measurements from combined EPIC, OMPS, OMI, and Microwave Limb Sounder (MLS) satellite instruments. A primary motivation is to show that there were large planetary-scale decreases of NH tropospheric ozone in year 2021 that were similar to the decreases in year 2020.…”
mentioning
confidence: 99%
“…However, the trend of benzene was similar to PBLH which is common in urban regions. 48 After the event, around 21:30 h, within 20 min, it was observed that the PM 2.5 levels rose suddenly from 66 μg m −3 to 95–100 μg m −3 (Fig. 4), whereas the concentration of PM 2.5 at night generally ranged between 40 and 55 μg m −3 during P1 of the lockdown (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…However, the trend of benzene was similar to PBLH which is common in urban region. 48 After the event, around 21:30 h, within 20 min, it was observed that the PM 2.5 levels rose suddenly from 66 µg/m 3 to 95-100 µg/m 3 (Figure 4), whereas the concentration of PM 2.5 at night generally ranged between 40-55 µg/m 3 during P1 of the lockdown (Figure 3 (upper panel)). Additionally, the concentration of benzene showed a similar diurnal pattern as PM 2.5 with concentration 2.3 ± 0.6 µg/m 3 during the day and 2.5 ± 0.4 µg/m 3 during the night in the course of P1 of the lockdown, while, on April 5, 2020 following the Lamp event, the night levels of benzene rose to 3.9 µg/m 3 , indicating the additional source of pollutants in the same environment.…”
Section: Diurnal Variation Of Pm 25 and Benzene Along With Pblh Durin...mentioning
confidence: 95%
See 1 more Smart Citation